1988
DOI: 10.1139/m88-029
|View full text |Cite
|
Sign up to set email alerts
|

Suppression by the ColV,I-K94 plasmid of inhibitor sensitivities in ompA mutants of Escherichia coli

Abstract: A series of ompA mutants derived from Escherichia coli K12 strains showed increased sensitivity (compared with the ompA+ parents) to aminoglycoside antibiotics and to other cationic agents including polymyxin B. One tested mutant also showed increased sensitivity to nafcillin and fusidic acid, but not to the hydrophilic ampicillin. All these inhibitor sensitivities in the ompA mutants were suppressed by ColV, I-K94 and by certain other ColV plasmids, but not by any of the other tested large plasmids. Suppressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1989
1989
1996
1996

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…(relA); CF1652 PALS10 (CFl652 relA+); TA15 (melBLid, rpsL, A 1ucZY); NM81 (TA15 nhuA, KanK); AB2847 (tsr, mulT, aroB); H2300 (AB2847 A tonB); 6482 leuB6,tonA23,luc Y I ,proC83,purE42,supE44,galK2,trpE38,UJbDI,urg77,rpsLI09,ilvA681,metA160,7157 (6482 katF3,sthAIS,glpR201,kafCI6); HN678 (gulK2,sup0,strR, (Reakes et al 1988) showed no trace of OmpC protein.…”
Section: Bacterial Strainsmentioning
confidence: 99%
“…(relA); CF1652 PALS10 (CFl652 relA+); TA15 (melBLid, rpsL, A 1ucZY); NM81 (TA15 nhuA, KanK); AB2847 (tsr, mulT, aroB); H2300 (AB2847 A tonB); 6482 leuB6,tonA23,luc Y I ,proC83,purE42,supE44,galK2,trpE38,UJbDI,urg77,rpsLI09,ilvA681,metA160,7157 (6482 katF3,sthAIS,glpR201,kafCI6); HN678 (gulK2,sup0,strR, (Reakes et al 1988) showed no trace of OmpC protein.…”
Section: Bacterial Strainsmentioning
confidence: 99%
“…Calvo; strains JA199 (trpE5, leu-6, thi, hsdR, hsdM+) and NK1 UA199 cysB) from D r N. Kredich. Strains 1157-4 (1157phoE+,proA+), RJR203 (thr, leu, thi, lacy, ara, ,rjd, rpsL, lamB, ompA2101, colv, 1-K94), 1829, 1 829-TetR (1 829 Izimd, tetracycline-resistant), 1829-KanR' (1829 fur, kanamycin-resistant), 1829-KanR3 (1829 nhaA, kanamycin-resistant) and 1829-AmpR (1829 hns, ampicillin-resistant) were all produced in this laboratory and have been described previously (Reakes et al 1988 ;Rowbury and Hussain 1996;. Strains MC4100 PALS 10 and AT142 PALS10 were made by transformation with PALS10 DNA and strain TA15 pJP102 by transformation with pJP102 DNA (see below).…”
Section: Bacterial Strainsmentioning
confidence: 99%
“…After setting, phage K3 suspensions were dropped onto the agar surfaces and plates incubated for 20-30 h at 37°C. Colonies growing in the cleared areas were purified and membranes tested from OmpA protein as described by Reakes et al (1988).…”
Section: Assessment Of Sensitivity To Phage K3mentioning
confidence: 99%